Influence of radiopacifier additives on calcium aluminate cement properties - Ivone Regina de Oliveira; Talita Luana de Andrade; Daniele Coelho Matsuo; Renata Martins Parreira; Marcos Jacobovitz; Victor Carlos Pandolfelli (Materials Research, 2014)
The aim of this study was to determine the best radiopaque additive to be incorporated to calcium aluminate cement (CAC) to promote radiopacity. Measurements of optical density were carried out on white MTA and CAC with and without additives such as: polymeric dispersant, plasticizer and various radiopacifiers. The effects of the radiopacifying addition on some properties of CAC were also evaluated. The radiopacity value for CAC-Bi2O3 (25%) was higher than the other radiopacifying agents tested. The addition of ZnO (25%) and 15%ZnO:10%Bi2O3 increased the compressive strength of CAC, whereas for Bi2O3 (25%) containing samples the strength was lower than for the CAC. The ZnO (25%) and 15%ZnO:10%Bi2O3 additions also reduced the apparent porosity. CAC does not have sufficient radiopacity to be distinguished from adjacent anatomic structures, such as dental tissues and bone. The addition of 15%ZnO:10%Bi2O3 can be suggested as the most suitable one to obtain the best compromise between good physical and mechanical properties and ideal radiopacity for clinical purposes.